The politics of fertilizer supply to agriculture: Analysis of political actors, discourses, and strategies - Gupta, Surupa (International Food Policy Research Institute, 2011)
This chapter begins by presenting stakeholder positions, as gleaned from interviews (see Table 3.1) and published sources. The literature presented in Chapter 2 and the conceptual framework presented in Chapter 3 provided guidance for the data gathering and analysis presented in this chapter. The first section describes the major actors and their interests as well as their political resources and strategies. The second section discusses the role of interests and institutions in fertilizer-sector reform. The third section identifies major discourse coalitions and describes their belief systems and discourses. The fourth section reflects on the extent of policy learning across coalitions. This chapter provides the basis for an analysis of the political feasibility of different reform options and strategies, which is presented in Chapter 7.